Fiqh Nusantara: al-Qawmiyyah al-Muʿāṣirah wa Taḥawwulāt Makānat al-ʿUrf fī al-Fiqh al-Islāmī - Rusydi, Hasan; Rifat, Muhammad (Al-Zahra : Journal for Islamic and Arabic Studies, 2024)
The discourse of ‘urf in Islamic fiqh has been a topic of discussion and attention in recent years. One of the related discourses is the emergence of Fiqh Nusantara as part of the Islam Nusantara discourse that was established and promoted by Nahdlatul Ulama in its Congress held in Jombang in 2015. This discourse is an effort to renew Islamic fiqh by paying more attention to local customs, the prevailing ‘urf, as well as the diverse cultures in Indonesia. Fiqh Nusantara uses the theory of ‘urf as the main method to understand shar‘i texts and formulate Islamic laws. This research also compares the theory of ‘urf in Fiqh Nusantara with the discussion of classical scholars in the treasures of Islamic fiqh and examines how Orientalists study this theory. This research highlights how the concept of ‘urf underwent a transformation, from being considered as an independent argument, following other valid arguments, to an independent argument equal to the Qur’an, Hadith, Ijma‘, and Qiyas. In addition, this research also examines how Orientalist and modernist studies influenced this change in concept, as well as how modern nation-states transformed ‘urf from a mere source of shar‘i law in Islamic fiqh to a symbol of national identity that every country should build and be proud of. This transformation is even used as a differentiator between one country and another around the world.